(untitled) (Andamios, Revista de Investigación Social, 2025)
Self-regulation is a process that is highly important in the academic field given its impact on learning achievement. The objective of this study is to know the self-regulation process that university students carry out to fulfill their academic activities. To this end, interviews were conducted with 14 university students from different majors and semesters selected in a non-probabilistic manner. Among the main findings, students mention that they use different self-regulation strategies; however, these strategies decrease in each of the phases of the academic self-regulation process (planning, monitoring, control, and self-assessment). That is, some students plan their academic objectives, but to a lesser extent they verify whether they finally achieved them or not.